How to write proposals,sales letters and reports - Sawers, Neil (New Delhi : Viva Books Pvt.Ltd, 2009)
"In today,s world, whatever your role, you spend a significant amount of your time selling yourself, your ideas and your products to your friends, customers and co-workers. How to communicate this information in a structured form. whether written or oral, is an art form that we all need to be good at" "How to write proposals, sales letters and reports" shows us how to apply a practical, systematic approach that will definitely lead to better communication and to higher levels of success."
Includes bibliographical references and appendix.
Keywords: Business communication & presentation; Writing skills; Writing & editing guides